Self-reflective dramaturgy in Rossini´s comic operas - Birbili, Maria (Música em Perspectiva, 2013)
My article discusses Rossini's comic operas by investigating the specific means with which humour, in the way of comedy, parody, and ironic distance is achieved by Rossini and his librettists. In addition to the traditional use of comedic techniques with a direct provenance in the spoken theatre or in the commedia del arte (such as verbal repetition, puns, and slapstick), I discuss how Rossini uses self-reflective techniques in the plot devices, the dramatic situations, and particularly in his deliberate use of specific formal structures in the music which either intensify or completely negate the dramatic situation at hand. More specifically with the use of crescendo, sonata form, and the deliberate slowing down of dramatic action in a critical dramatic situation through repetitive vocal embellishments for comic relief, while even the characters on stage self-reflectively complain about this. This self-reflective dramaturgy exploits the dynamic between com-poser, performers, and audience, and creates new possibilities in interdependence between the deliberate use of artifice and the detection and appreciation of artifice by the audience. The self-reflection results in presenting the dramatic situation and its musical setting as a meta-comment on the traditional formal structures of Italian opera itself.